Familial occurrence of mitral regurgitation in patients with mitral valve prolapse undergoing mitral valve surgery. (February 2020) - Hiemstra, Yasmine L; Wijngaarden, Aniek L van; Bos, Mathilde W; Schalij, Martin J; Klautz, Robert JM; Bax, Jeroen J; Delgado, Victoria; Barge-Schaapveld, Daniela QCM; Marsan, Nina Ajmone
Background: Initial studies have suggested the familial clustering of mitral valve prolapse, but most of them were either community based among unselected individuals or applied non-specific diagnostic criteria. Therefore little is known about the familial distribution of mitral regurgitation in a referral-type population with a more severe mitral valve prolapse phenotype. The objective of this study was to evaluate the presence of familial mitral regurgitation in patients undergoing surgery for mitral valve prolapse, differentiating patients with Barlow's disease, Barlow forme fruste and fibro-elastic deficiency. Methods: A total of 385 patients (62 ± 12 years, 63% men) who underwent surgery for mitral valve prolapse were contacted to assess cardiac family history systematically. Only the documented presence of mitral regurgitation was considered to define 'familial mitral regurgitation'. In the probands, the aetiology of mitral valve prolapse was defined by surgical observations. Results: A total of 107 (28%) probands were classified as having Barlow's disease, 85 (22%) as Barlow forme fruste and 193 (50%) patients as fibro-elastic deficiency. In total, 51 patients (13%) reported a clear family history for mitral regurgitation; these patients were significantly younger, more often diagnosed with Barlow's disease and also reported more sudden death in their family as compared with 'sporadic mitral regurgitation'. In particular, 'familial mitral regurgitation' was reported in 28 patients with Barlow's disease (26%), 15 patients (8%) with fibro-elastic deficiency and eight (9%) with Barlow forme fruste ( P < 0.001). Conclusions: In a large cohort of patients operated for mitral valve prolapse, the self-reported prevalence of familial mitral regurgitation was 26% in patients with Barlow's disease and still 8% in patients with fibro-elastic deficiency, highlighting the importance of familial anamnesis and echocardiographic screening in all mitral valve prolapse patients.